CCN6 Knockdown Disrupts Acinar Organization of Breast Cells in Three-dimensional Cultures through Up-regulation of Type III TGF-β Receptor - Pal, Anupama (Neoplasia Press Inc., 2012)
While normal cells in the human breast are organized into acinar structures, disruption of the acinar architecture is a hallmark of cancer. In a three-dimensional model of morphogenesis, we show that down-regulation of the matrix-associated tumor suppressor protein CCN6 (WNT1-inducible-signaling pathway protein 3) disrupts breast epithelial cell polarity and organization into acini through up-regulation of the type III transforming growth factor-β receptor (TβRIII or betaglycan). Down-regulation of CCN6 in benign breast cells led to loss of tissue polarity and resulted in cellular disorganization with loss of α6 integrin-rich basement membrane and the basolateral polarity protein E-cadherin. Silencing of TβRIII with shRNA and siRNA rescued the ability of breast epithelial cells to form polarized acinar structures with reduced matrix invasion and restored the correct expression of α6 integrin and E-cadherin. Conversely, CCN6 overexpression in aggressive breast cancer cells reduced TβRIII in vitro and in a xenograft model of CCN6 overexpression. The relevance of our studies to human breast cancer is highlighted by the finding that CCN6 protein levels are inversely associated with TβRIII protein in 64%of invasive breast carcinomas. These results reveal a novel function of the matricellular protein CCN6 and establish a mechanistic link between CCN6 and TβRIII in maintaining acinar organization in the breast.